The relationship between healthy lifestyle score and incident cardiovascular disease: results from Isfahan Cohort Study (ICS) - Shahnaz Amani Tirani; Parisa Hajihashemi; Motahare Bateni; Noushin Mohammadifard; Fahimeh Haghighatdoost; Maryam Boshtam; Jamshid Najafian; Masoumeh Sadeghi; Mansoureh Boshtam; Nizal Sarrafzadegan (Archives of Public Health)
Abstract Background Evidence on the combined impact of healthy lifestyle factors on cardiovascular disease (CVD) risk in the Iranian population is limited. This study aimed to examine the association between a healthy lifestyle score (HLS) and the incidence of CVD. Methods This prospective cohort study, including 5419 adults aged over 35 years, was performed in the framework of the Isfahan Cohort Study (ICS) which is an ongoing study. The HLS (ranging from 0 (unhealthy) to 4 (most healthy)) was derived from four modifiable risk factors: never smoking, diet quality, physical activity, and body mass index (BMI). Investigated cardiovascular outcomes included myocardial infarction (MI), stroke, unstable angina (UA), and CVD mortality. Cox proportional hazards regression models were used to estimate hazard ratios (HR) and assigned 95% confidence intervals (CI). Results Over a median follow-up of 11.25 years, 785 CVD events occurred, including 159 MI, 164 stroke, 369 UA, and 172 CVD deaths. In the fully-adjusted model, participants with the highest HLS (3–4) had a significantly lower risk of stroke (HR: 0.51; 95% CI: 0.31–0.83; P trend = 0.019) and a tendency towards lower risk of CVD (HR: 0.78; 95% CI: 0.61–0.98; P trend = 0.053) compared to individuals with the lowest HLS (0–1). No significant association was found for MI, UA, or CVD mortality. Age- and sex-specific patterns were also noted for stroke and overall CVD. Conclusion Our results suggest that a healthier lifestyle was linked to a reduced risk of stroke and showed a trend toward lower CVD risk among Iranian adults. These associations may vary by age and sex.